The influence of experiential marketing and brand commitment on repurchase intention with satisfaction as intervening variables - Seski Nadila Arani; Yunita Engriani (Marketing Management Studies, 2022)
The purpose this study is to analyze: (1) The Effectt Experiential Marketing on Repurchese Intentionn through Satisfaction as an Intervening Variable. (2) The influence of Brand Commitment on Repurchese Intention through Satisfaction as an Intervening Variable. The population in this study were Kupi Batigo consumers in the period 2021. The sampling technique this study was Purposive Sampling with a total sample of 105 respondents in 2021. The data used in this study was primary data obtained through distributing questionnaires to Kupi Batigo visitors. . The results this study indicate that: (1) Experiential Marketing has a significant positive effect on satisfaction. (2) Brand Commitment has a significant positive effect on satisfaction. (3) Satisfaction has a significant positive effectt on Repurchese Intentian.